The librarian Luisa Cuesta Gutiérrez (1892-1962) - Egoscozábal Carrasco, Pilar; Mediavilla Herreros, María Luisa (Revista General de Información y Documentación, 2012)
Luisa Cuesta Gutiérrez, a member of the High Council of Civil Archivists, Librarians and Archaeologists, was a model of modern woman who fought against the socioeconomic conditions in the beginning of the XX century to develop a brilliant career as a teacher, researcher and especially as a librarian, working at National Library. She played an active role during the Spanish Civil War as a member of the Interim Committee of the High Council and she was purged when the war finished. Her biographical and professional profiles are shown, the second one expressed in a significant bibliographical work covering different subjects, from historical research to feminism, and focused, in her final stage, on printing history. In this sense, the elaboration of two bibliographies which were later completed: Printing in Salamanca and Printing in Burgos, is outstanding.
Keywords: Luisa Cuesta Gutiérrez; Spanish Civil War; High Council of Civil of Archivists; Librarians and Archaeologists; Civil servants’ purge; National Library of Spain.